FLOWERS IN A CLOSED ENVIRONMENT - Abdusamatov Ne’mat Inomovich (Journals Park Publishing, 2022)
Particular attention should be paid to the types of plants and flowers in the organization of the indoor landscape. Depending on the biological structure of the panel, it is necessary when the plants live in the interior. The article contains many solutions of many types of flowers that are useful for human health, how to take the file and how to transplant them.
Keywords: philodendron, purple, pelargonium, indoor flowering, transplant.